ANALISIS IMPLEMENTASI PENDEKATAN DEEP LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MURID DI KELAS X SMAN 1 GIRI - NUR AFIFAH ERMAWATI (FKIP, 2026)
The Deep Learning approach emphasizes meaningful learning, mindful learning, and joyful learning, enabling students to develop a deeper understanding of concepts, connect knowledge with real-life experiences, and enhance higher-order thinking skills. One of the essential higher-order thinking skills fostered through this approach is creative thinking. However, preliminary observations conducted in Grade X at SMAN 1 Giri revealed that students' creative thinking skills were still relatively low, particularly in the indicators of originality and elaboration. Therefore, the implementation of the Deep Learning approach in mathematics instruction was considered necessary to facilitate the development of students' creative thinking skills. This study aimed to describe the implementation of the Deep Learning approach in mathematics learning and to determine the improvement in students' creative thinking skills after its implementation. This study employed a pre-experimental method using a One-Group Pretest–Posttest Design. The participants consisted of 36 tenth-grade students at SMAN 1 Giri selected through purposive sampling. Data were collected using a creative thinking skills test, an observation sheet on the implementation of learning, and documentation. The data were analyzed descriptively using mean scores, the percentage of learning implementation, and the Normalized Gain (N-Gain). The findings indicated that the implementation of the Deep Learning approach was carried out very well, achieving a learning implementation rate of 98%. Students' creative thinking skills improved from a mean pretest score of 6.39 to a mean posttest score of 10.36. The average N-Gain score was 0.45, which falls into the medium category with a tendency toward the low category, indicating that the improvement in students' creative thinking skills was not yet optimal. Based on the analysis of each indicator, the greatest improvement was found in the elaboration and fluency indicators, followed by flexibility, whereas the originality indicator showed no improvement. It can be concluded that the Deep Learning approach contributes to improving students' creative thinking skills in mathematics learning, although the improvement has not been optimal across all indicators. These findings suggest that implementing the Deep Learning approach over more than one instructional session may lead to a more significant and evenly distributed improvement in students' creative thinking skills across all indicators.
Finalisasi Juli 2026 hasyim
Keywords: Deep Learning; Creative Thinking Skills; Mathematics Learning; Sequences and Series; Wilcoxon Signed-Rank Test